2023
DOI: 10.2147/ijn.s406864
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cosmeceutical Potentials of the Oil from Gryllus bimaculatus de Geer by Nanoemulsions

Wantida Chaiyana,
Sudarat Jiamphun,
Suchanan Bezuidenhout
et al.

Abstract: Purpose This study aimed to extract the oil from Gryllus bimaculatus de Geer, evaluate its potential for cosmeceutical applications, and develop nanoemulsions to promote the cosmeceutical capabilities of the oil. Methods G. bimaculatus oil was produced by the cold pressing method. Its fatty acid compositions were assessed by fatty acid methyl ester/gas chromatographic-mass spectrometry. The antioxidant activities of the oil were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Therefore, A. domesticus has great potential to be used as a bioactive cosmeceutical ingredient. Its potential as an appealing source of bioactive cosmeceutical ingredients lies in its capacity to breed in a brief 45-day timeframe, the ease of the breeding process, its suitability for small-scale production, minimal investment needs, and the absence of advanced technology prerequisites [ 87 ]. It could enhance the agricultural economic prospects of cricket farming and create a valuable opportunity to generate bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, A. domesticus has great potential to be used as a bioactive cosmeceutical ingredient. Its potential as an appealing source of bioactive cosmeceutical ingredients lies in its capacity to breed in a brief 45-day timeframe, the ease of the breeding process, its suitability for small-scale production, minimal investment needs, and the absence of advanced technology prerequisites [ 87 ]. It could enhance the agricultural economic prospects of cricket farming and create a valuable opportunity to generate bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, variations in the order of abundance among palmitic acid, oleic acid, and linoleic acid introduce specific differences, yet these three fatty acids consistently remain the primary constituents. For example, Chaiyana et al (2023) reported that G. bimaculatus oil was rich in linoleic acid (31.08 ± 0.00%), followed by oleic acid (30.44 ± 0.01%) and palmitic acid (24.80 ± 0.01%) [ 14 ], whereas Gan et al (2022) reported that the oil was rich in linoleic acid (41.75 ± 0.23%), followed by palmitic acid (24.31 ± 0.14%) and oleic acid (22.75 ± 0.09%) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, variations in the order of abundance among palmitic acid, oleic acid, and linoleic acid introduce specific differences, yet these three fatty acids consistently remain the primary constituents. For example, Chaiyana et al ( 2023) reported that G. bimaculatus oil was rich in linoleic acid (31.08 ± 0.00%), followed by oleic acid (30.44 ± 0.01%) and palmitic acid (24.80 ± 0.01%) [14], whereas Gan et al (2022) reported that the oil was rich in linoleic acid (41.75 ± 0.23%), followed by palmitic acid (24.31 ± 0.14%) and oleic acid (22.75 ± 0.09%) [31]. As the Fourier transform infrared spectrometer (FT-IR) offers advantages over conventional qualitative and quantitative analysis methods in terms of ease of sample handling, shorter analysis duration, reduced solvent use, improved signal-to-noise ratio, simultaneous recording of all wavelengths, and no need for high energy [32], it was used for chemical profile characterization of each cricket oil.…”
Section: The Chemical Profiles Of Cricket Oilsmentioning
confidence: 99%
See 2 more Smart Citations